What is political in the colombian civil war (2011)
The basic argument of the article controverts the idea that the low social representativeness and the interested motives of the armed actors disqualify them as political actors. It is supported by the friend/enemy Schmittian distintion to argue that a civil war is always political -independently of motives by the parties—, inasmuch as the intensity of enmity gives preference to the animus bel li over the animus furandi. The article points out —in concordance with the proposal of Stathis Kalyvas- that social representativeness of the contending parties is endogenous to the civil war and cannot be used as a previous criterion for its identification. The concealment of the Colombian civil war portrays the intention of exculpating the elites and the society.